Democratic professionals in civic life: cultivating civil discourse in community development. Issue 3 (26th May 2020) - Shaffer, Timothy J.
ABSTRACT: The field of community development is challenged in the current political culture where polarization and incivility impact democratic ideals and practices. The role of the community development practitioner in such an environment is to approach one's work as a civic professional, using technical expertise in public-regarding ways to cultivate opportunities for discussion across lines of difference. Foundational and functional competencies for community development include many important characteristics, but they do not include explicit language addressing political polarization. The article suggests looking to educational and professional development programs in the field of dialogue and deliberation as a way to further develop and refine these competencies.